Clinical and epidemiological aspects in Timor patients with the Hansen disease - María Elena Tablada Robinet; Haidee Marrero Rodríguez; Natacha López Pupo; Dianelis Mulén Tablada; Oleidis Pérez González (Centro Provincial de Información de Ciencias Médicas, 2019)
An observational, descriptive and cross-sectional study of 14 patients with leprosy, diagnosed and assisted in the Dermatology Service of "Guido Valadares" National Hospital, in Dili, Timor Lester was carried out from July to December, 2015, with the aim of characterizing them and to describe some clinical and epidemiological aspects of the disease. In the series a higher frequency of patient was obtained in the age group 26 to 35 years and of the male sex, the predominant clinical form was the multibacilar and the time of clinical course of the symptoms up to reaching the diagnosis was shorter than a year. Equally, in most of them acute reactions were presented, mainly of type II or from the erythema leprosy group, and different degrees of inability.